Analisa Beban Kerja dan Studi Waktu Kerja Guna Optimalisasi Proses Produksi: Studi Kasus CV. XYZ - Putra, Vi'ar Aprisa; Satoto, Handy Febri (Fakultas Teknik UMRI, 2025)
This study aims to analyze workload and working time to optimize the production process. CV. XYZ is a small and medium enterprise that produces soy sauce. This company faces obstacles in meeting demand due to limited labor, manual production processes, and high workload and imbalanced distribution. Measuring the level of physical workload using the Cardiovascular Load (CVL) Method and energy consumption found fatigue in the boiling process, filling process and packaging process, while measuring standard time using the Work Sampling method produces a time of 112.42 seconds for each bottle. optimization Workload Analysis (WLA) recommended decreasing the number of labeling employees from 9 to 4 workers and raising the number of packing employees from 3 to 8 workers. The study comes to the conclusion that either more workers or longer workdays are needed to increase productivity. The goal of these suggestions is to promote sustainable production capacity.